(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Infrastructure development near the riverside possess lot of hydrological problems. Thiscurrent research reviews various aspects of bridge engineering, river management, and foundationanalysis. The studies are based on the challenges and complexities associated with bridge construction,maintenance, and restoration, highlighting the need for advanced methodologies and comprehensiveevaluations. The analysis encompasses topics such as historical bridge designs, river sensitivity, soilwellinteraction, and the dynamic response of structures under lateral loads.